Power-to-X in energy hubs: A Danish case study of renewable fuel production. (April 2023) - Kountouris, Ioannis; Langer, Lissy; Bramstoft, Rasmus; Münster, Marie; Keles, Dogan
Abstract: The European Commission recently proposed requirements for the production of renewable fuels as these are required to decarbonize the hard-to-electrify parts of the industrial and heavy transport sectors. Power-to-X (P2X) energy hubs enable efficient synergies between energy infrastructures, production facilities, and storage options. In this study, we explore the optimal operation of an energy hub by leveraging the flexibility of P2X, including hydrogen, methanol, and ammonia synthesizers by analyzing potential revenue streams such as the day-ahead and ancillary services markets. We propose EnerHub2X, a mixed-integer linear program that maximizes the hub's profit based on current market prices, considering the technical constraints of P2X, such as unit commitment and non-linear efficiencies. We investigate a representative Danish energy hub and find that without price incentives, it mainly sells renewable electricity and produces compressed hydrogen. A sufficient amount of renewable ammonia and methanol is only produced by adding a price premium of about 50% (0.16 €/kg) to the conventional fuel prices. To utilize production efficiently, on-site renewable energy sources and P2X must be carefully aligned. We show that renewable power purchase agreements can provide flexibility while complying with the rules set by the European Commission. Highlights: We propose a new multi-carrier energy systems model to analyze Power-to-X in energy hubs. We investigate optimal operation for different expansion configurations and markets. We evaluate the profitability of operating energy hubs under current market conditions. We analyze different policy scenarios to promote renewable fuel production. We illustrate the dispatch merit order for varying levels of renewable fuel premiums.